ANALYSIS OF ALLUSIONS IN ABDULLA QODIRY’S O‘TGAN KUNLAR (KONFERENSIYA, 2025)
Abdulla Qodiry’s O‘tgan kunlar (1925) is regarded as the first full-fledged Uzbeknovel and a foundational work of modern Uzbek literature. The novel is rich withallusions indirect references to historical, religious, literary, and cultural sources thatdeepen its ideological message and connect the fictional world to the real social,moral, and spiritual struggles of the late 19th century. This article explores the majortypes of allusions in the novel, analyzing their functions, meanings, and artisticeffects within the narrative